2021
DOI: 10.1101/2021.07.27.453855
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thalamic deep brain stimulation as a paradigm to reduce consciousness: implications for cortico-striatal dynamics, absence epilepsy and consciousness studies

Abstract: Anesthetic manipulations provide much-needed causal evidence for neural correlates of consciousness, but nonspecific drug effects complicate their interpretation. Evidence suggests that thalamic deep brain stimulation (DBS) can either increase or decrease consciousness, depending on the stimulation target and parameters. The putative role of the central lateral thalamus (CL) in consciousness makes it an ideal DBS target to manipulate circuit-level mechanisms in corticostriatothalamic (CST) systems, thereby inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…It is characterized by complex partial seizures, and secondary generalizations resulting from abnormal electrical activity in the temporal lobe, presenting as epileptic foci ( 3 , 4 ). The recurring seizures in most people with TLE, result in cognitive dysfunction in areas such as learning, language, memory, emotion, perception, attention, consciousness, and behavior, which has a serious impact on their cognitive abilities and their lives ( 5 7 ). Existing studies have shown that the pathogenesis of epilepsy can be further understood through the study of the brain network properties, and interactions between different brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by complex partial seizures, and secondary generalizations resulting from abnormal electrical activity in the temporal lobe, presenting as epileptic foci ( 3 , 4 ). The recurring seizures in most people with TLE, result in cognitive dysfunction in areas such as learning, language, memory, emotion, perception, attention, consciousness, and behavior, which has a serious impact on their cognitive abilities and their lives ( 5 7 ). Existing studies have shown that the pathogenesis of epilepsy can be further understood through the study of the brain network properties, and interactions between different brain regions.…”
Section: Introductionmentioning
confidence: 99%